Biomarkers of Thrombo-Inflammatory Responses in Pulmonary Embolism Patients With Pre-Existing Versus New-Onset Atrial Fibrillation - Dimpi Patel BA; Amir Darki MD; Debra Hoppensteadt PhD; Iman Darwishw BA; Mushabbar Syed MD; Yevgeniy Brailovsky DO; Jawed Fareed PhD (Clinical and Applied Thrombosis/Hemostasis, 2021)
Pulmonary embolism (PE) patients have an increased prevalence and incidence of atrial fibrillation (AF). Because comorbid AF increases risk of morbidity and mortality, we sought to investigate the role of thrombo-inflammatory biomarkers in risk stratifying patients who experience an acute PE episode. Study participants were enrolled from a Pulmonary Embolism Response Team (PERT) registry between March 2016 and March 2019 at Loyola University Medical Center and Gottlieb Memorial Hospital. This cohort was divided into 3 groups: PE patients with a prior diagnosis of AF (n = 8), PE patients with a subsequent diagnosis of AF (n = 11), and PE patients who do not develop AF (n = 71). D-Dimer, CRP, PAI-1, TAFIa, FXIIIa, A2A, MP, and TFPI were profiled using the ELISA method. All biomarkers were significantly different between controls and PE patients ( P < 0.05). Furthermore, TFPI was significantly elevated in PE patients who subsequently developed AF compared to PE patients who did not develop AF (157.7 ± 19.0 ng/mL vs. 129.0 ± 9.3 ng/mL, P = 0.0386). This study suggests that thrombo-inflammatory biomarkers may be helpful in indicating an acute PE episode. Also, elevated TFPI levels may be associated with an increased risk of developing AF after a PE.